Mavacamten maintenance dose determination: insights into individualised therapy for hypertrophic cardiomyopathy - Kawa Mohemed; Smita Scholtz; Volker Rudolph; Jan-Christian Reil; Max Potratz; Cédric Coppée; Vasco Sequeira; Werner Scholtz (Open Heart)
Aims Mavacamten, the first approved myosin inhibitor for symptomatic obstructive hypertrophic cardiomyopathy (oHCM), addresses hypercontractility and left ventricular outflow tract (LVOT) obstruction. This study evaluates real-world experience with mavacamten, focusing on maintenance dose determination to optimise individual therapy and enhance patient safety.Methods 36 patients with symptomatic oHCM who completed the initiating phase of mavacamten therapy were analysed. CYP2C19 genetic testing determined metabolic status prior to treatment. Echocardiographic measurements (eg, LVOT gradient, left atrial volume index, left ventricular ejection fraction (LVEF) and E/E’) and biomarkers (high-sensitivity troponin I, N-terminal pro B-type natriuretic peptide (NT-proBNP)) were assessed at baseline and after 3 months. Clinical status was evaluated using New York Heart Association (NYHA) class and Kansas City Cardiomyopathy Questionnaire (KCCQ) score.Results The mean age of patients was 60.6±12.1, and all had normal CYP2C19 metabolic status. LVEF was 68% (IQR 8) at baseline and decreased mildly to 60.5% (IQR 7.25; p=0.0004) without cases dropping below 50%. Resting and provoked LVOT gradients decreased from 65 mm Hg (IQR 43.75) and 105 mm Hg (IQR 36.25) to 12 mm Hg (IQR 15.5; p<0.001) and 52.5 mm Hg (IQR 46.5; p<0.001), respectively. NT-proBNP and high-sensitivity troponin I decreased significantly from 1040 ng/mL (IQR 1255) to 285 ng/mL (IQR 483; p=0.0005) and from 11 ng/mL (IQR 15.5) to 10 ng/mL (IQR 5; p<0.0001). Diastolic function improved slightly; and clinically, patients improved significantly, with improvement in NYHA class and increase in KCCQ score. Mean time to reach maintenance dose was 14 weeks, with the necessity of dose adjustments in more than 50% of cases.Conclusion Mavacamten therapy is safe and effective in the initiating phase. Determination of starting and maximum dose is based on CYP2C19 metabolic status, while individualised dose adjustments are guided by echocardiographic response to optimise patient safety.